A Six-Month Evaluation of the Vivasight™ Video Double-Lumen Endotracheal Tube after Introduction into Thoracic Anaesthetic Practice at a Single Institution. Issue 2 (March 2017) - Rapchuk, I. L.; Kunju, S. A. M.; Smith, I. J.; Faulke, D. J.
For a six-month period, all airway options used for non-emergent patients undergoing thoracic surgery requiring one-lung ventilation at a single institution were assessed after introduction of the VivaSight™ double-lumen endotracheal tube (VivaSight-DL), a novel double-lumen tube with an integrated camera. This device displays a continuous view of the position of the tube relative to the carina. A total of 72 patients had lung separation with the VivaSight-DL. Lung separation was achieved on first attempt without additional manipulation in 85% of cases. In only three cases (4%) was a fibreoptic bronchoscope required, in each instance to reposition the tube after intraoperative dislodgement. The VivaSight-DL represents a novel method of one-lung ventilation allowing rapid identification of intraoperative airway problems and reducing the need for fibreoptic bronchoscopy.